Etiology, development and reaction of muskmelon to vine decline under arid conditions of Oman - Al-MAWAALI, Qais Saif; Al-SADI, Abdullah; Al-SAID, Fahad; DEADMAN, Mike (Phytopathologia Mediterranea, 2013)
Muskmelon vine decline is considered the most important factor limiting muskmelon production in Oman. This study was conducted to characterize incidence, development, causal agents and response of muskmelon cultivars to this disease. A survey showed that incidence of the disease ranged from 0 to 15% (mean 5%) in spring 2011, 1 to 80% (mean 18%) in autumn 2011 and 0 to15% (mean 10%) in spring 2012. Isolations from 168 affected plants yielded Pythium aphanidermatum (56% of diseased plants sampled), Fusarium spp. (46%), Monosporascus cannonballus (27%), Rhizoctonia solani (22%) and Macrophomina phaseolina (1%). In pathogenicity tests, R. solani, M. cannonballus and P. aphanidermatum were found to be pathogenic to muskmelon. In another experiment over three seasons, M. cannonballus, P. aphanidermatum and R. solani were consistently isolated from muskmelon plants on a weekly basis from 14 days after sowing until the end of the season. However, symptom development only began with the onset of fruiting, which suggests that fruiting stress may be a factor in vine decline disease development. Field assessment of 11 muskmelon cultivars showed that ‘Shahd F1’ was one of the cultivars least susceptible to vine decline and was relatively high yielding. This is the first record of M. cannonballus as a causal agent of muskmelon vine decline in Oman.